ISLAMIC EDUCATION INSTITUTION FINANCIAL PLANNING - Kartika, Dewi; Mujahidin, Endin; Indra, Hasbi; Indupurnahayu, Indupurnahayu; Andriana, Nesia (Idaarah: Jurnal Manajemen Pendidikan, 2023)
Financial planning and management has been carried out since the time of the Prophet Muhammad which became the forerunner to the application of the principles and functions of financial management in educational institutions today. This study aims to be able to analyze Islamic education financial planning, analyze the concept of financial planning in the Prophet’s shirah and analyze financial planning guidelines at educational institutions STIT Al-Hikmah Bumi Agung Way Kanan Lampung and STIT At-Taqwa Gegerkalong Bandung. This study uses a qualitative method with a descriptive analysis approach. The data is described and analyzed with a literature study approach. The results of the research show that in preparing financial planning it is necessary to apply the principles of financial management, have a legal basis, clear sources of funding, and carry out financial management functions. Educational institutions also have guidelines for financial planning and management of educational institutions, such as those found in the educational institutions of STIT Al-Hikmah Bumi Agung Way Kanan Lampung and STIT At-Taqwa Gegerkalong Bandung.